Gestão dos resíduos sólidos urbanos no Rio Grande do Sul: panorama com base no sistema nacional de informações sobre saneamento - Lopes, Izabel Cristine (2013)
The growth in the production of consumer goods has provoked an increase in the residue generation and consequently aggravated environmental problems due to inadequate disposal and so it has been discussed by researchers around the world. In Brazil, since 1995 the Ministry of Cities has maintained the National System (SNIS) about Sanitation, through the National Secretary of Sanitation, which organizes a diagnosis of the water and sewage system and since 2002 has incorporated data about solid residues, aiming at being a regulator and a guide for sanitation public policies. Upon approval of the Law 12.305 in August, 2010, a series of actions should have been conducted in Brazil, among them the creation of state and municipal management plans for solid residues in an attempt to improve the managing system. This research aimed at characterizing the management process of solid residues in Rio Grande do Sul, based on data available from SNIS. In order to do that, an analysis of the data from the cities from the years 2009 to 2011 was conducted. The results showed that there is lack of structure and other deficiencies for the management of solid residues. So as to tackle the problem, the Ministry of Cities should include other relevant data in SNIS and work with training so that the cities may be able to offer precise information since the information available is insufficient for broadening the management. However, it was verified that the cities have been evolving in managing practices, in the selective collection, in the introduction of trash collectors and in the implementation of consortiums. In general, it can be said that the cities in Rio Grande do Sul must evolve in many aspects in order to follow the Law 12.305/2010 and also evolve in the economic, administrative, social and environmental aspects